The role of CSR in luxury contexts : the influence of different luxury dimensions - Kuklis, Kamil (2016)
Today’s changing consumer behavior in favor of sustainability and environmental aspects issues a challenge to luxury brands, raising the question if these two concepts are compatible and which factors may affect consumer perceptions to corporate social responsibility (CSR) initiatives. This paper investigates the influence of luxury dimensions on the effectiveness of CSR communication and its connected brand value perception. In order to detect a potential relationship between these variables, a multi-scenario experiment was designed and conducted in form of an international online survey. The performed study reveals a clear trend that luxury dimensions have an impact on customers’ value perceptions in CSR related information schemes. However, the results indicate a significant constraint, showing that brands with more distinct luxury dimensions, hence higher perceived luxuriousness, experience stable or decreasing evaluations in value perception, whereas luxury brands with a low perceived degree of luxuriousness sense an overall increase in value perception when CSR information is available. Consequently the more luxurious a luxury company is perceived the less effective or even negative CSR communication impacts the value perception of a particular luxury brand. Yet a contradicting exception in form of the dimension history can be identified, showing reverse effects for brand evaluations. These findings imply that luxury dimensions are key drivers for the effectiveness of CSR communication, thus the value perception of a given luxury brand. Therefore, this study provides useful information for brand managers and marketing practitioners, working on CSR application strategies in the luxury industry.